2001
DOI: 10.3109/10428190109057927
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Zidovudine and Interferon AIpha-2B in the Treatment of Adult T-Cell Leukemia/Lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATL) is frequently a very aggressive malignancy with a poor survival despite aggressive multiagent chemotherapy. The combination of the antiretroviral drug zidovudine (AZT) and interferon alpha (IFNalpha) has been reported to induce remissions in patients with ATL. The purpose of this study was to evaluate the clinical response and toxicity following administration of a combination of IFNalpha-2b and AZT in patients with human T-cell lymphotropic virus type I (HTLV-I)-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 24 publications
2
34
1
1
Order By: Relevance
“…Antiviral therapy with zidovudine (AZT) and interferon-alpha (IFN-a) in these patients has produced longterm clinical remissions in human trials (Gill et al, 1995;Hermine et al, 1995;Matutes et al, 2001;White et al, 2001). In HTLV-I-infected cells, Tax stimulates endogenous hTERT promoter (Sinha-Datta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral therapy with zidovudine (AZT) and interferon-alpha (IFN-a) in these patients has produced longterm clinical remissions in human trials (Gill et al, 1995;Hermine et al, 1995;Matutes et al, 2001;White et al, 2001). In HTLV-I-infected cells, Tax stimulates endogenous hTERT promoter (Sinha-Datta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The efficacy of this combination was confirmed, with minor differences, in various clinical trials and in a worldwide meta-analysis. [12][13][14][15][16] These results changed the clinical management of ATL. [16][17][18][19] However, there is yet no direct proof of an antiviral mechanism of action of the drug combination, due to the absence of virological markers that strictly correlate with disease status.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66][67][68][69] Gill et al in the United States reported that treatment with AZT/IFN produced an objective response in 11 (five CR, six PR) of 19 patients with acute or lymphoma type ATL, 64 while a French group reported that the regimen produced an objective response in all five ATL patients that they treated. 65 Although the results with AZT/IFN are encouraging, the overall survivTreatment of ATL al of previously untreated ATL patients was rather short (4.8 mon) 66 when compared to those on the LSG15 regimen.…”
Section: New Chemical Anti-tumor Agents 1) Antiretroviral Therapymentioning
confidence: 99%